Penerapan Kombinasi Metode Pembobotan ROC dan SAW dalam Rekomendasi Media Marketing Bagi UMKM - Rahmanto, Yuri; Mesran; Sintaro, Sanriomi; Setiawansyah (Journal of Decision Support System Research, 2024)
Problems in choosing marketing media for MSMEs are often related to limited resources and knowledge. One of the main challenges is in choosing the right media platform according to the characteristics of their target market. Due to the large selection of social media and other digital channels, MSMEs often struggle to determine where they should focus or allocate their marketing budgets effectively. The application of a combination of ROC and SAW weighting methods in media marketing recommendations for MSMEs can provide more accurate and relevant results in the selection of promotional media. With this approach, MSMEs can more easily identify the most effective marketing media based on various factors such as cost, audience reach, and promotion effectiveness. The implementation of this combination of methods helps MSMEs in optimizing their marketing budgets, increasing the visibility of products or services, and ultimately, encouraging faster and more sustainable business growth Media marketing is essential for MSMEs to increase the visibility and sales of their products. Through the right combination of media marketing strategies, MSMEs can build strong brands, increase customer loyalty, and ultimately achieve sustainable business growth. The results of MSME media marketing recommendations using a decision support system approach using the ROC and SAW weighting methods show that the first rank with a final score of 0.7919 was obtained by Email Marketing, the second rank with a final score of 0.7314 was obtained by Tiktok Ads, and the third rank with a final score of 0.6908 was obtained by Facebook Ads.